Representing atrocity in Taiwan : the 2/28 incident and white terror in fiction and film - Lin, Sylvia Li-chun (Global Chinese culture., 2007)
In 1945, Taiwan was placed under the administrative control of the Republic of China, and after two years, accusations of corruption and a failing economy sparked a local protest that was brutally quashed by the Kuomintang government. The February Twenty-Eighth (or 2/28) Incident led to four decades of martial law that became known as the White Terror. During this period, talk of 2/28 was forbidden and all dissent violently suppressed, but since the lifting of martial law in 1987, this long-buried history has been revisited through commemoration and narrative, cinema and remembrance.>